Initiating the Reform of Principle Norms in the Formation of Laws in Indonesia - Asmarudin, Imam; Fauzan, Muhammad; Nasihuddin, Abdul Aziz; Ardhanariswari, Riris; Hariyanto, Hariyanto; Nunna, Bhanu Prakash (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The formation of responsive laws is an ideal form and a must in a country that adheres to democracy, the involvement of the community in the formation of laws and regulations is a form of implementation of democracy and popular sovereignty, so far the principles of the Formation of Legislation are regulated in Article 5 of Law Number 12 of 2011, but these principles are still formally operational and are considered unable to provide space for the community in conveying input that needs to be fulfilled in the mechanism of forming laws, so there needs to be an update on the principles of its formation. This research aims to find out how the idea of updating the norms of principles in the formation of laws in the future, the method in research uses legal research methods through approaches, data analysis is descriptive qualitative statute approach, conceptual approach, and case approach. the results of the study show that the formation of laws and regulations must certainly begin with a response to the existence of a legal problem that develops in society and there must be a regulatory solution, so that the formation of laws and regulations is not always based on political interests, certain groups or other interests, it is to avoid overregulation. The concept of responsiveness becomes urgent to be prioritized as a new norm of principles in the formation of good laws and regulations, because it can provide a two-way space between the legislator and the public quickly. the concept of responsiveness becomes a new idea in the new norm of the principles of good law formation, which has the character of strengthening the root foundation of the principle of openness and as a supporter (supporting) to the provisions of Article 96  Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Formation of Legislative Regulations.